Clinicopathological Spectrum of Chronic Filarial Epididymo-Orchitis: Experience from a Tertiary Care Institute - Paul, Preethi Anni Mercy; Kwatra, Kanwardeep Singh; Calton, Nalini; Chandler, Ekta; Mammen, Kim J (Annals of Pathology and Laboratory Medicine, 2018)
Background: Filariasis is a vector-borne neglected tropical disease, most commonly caused by Wuchereria bancrofti. Chronic lymphatic filariasis in males usually presents as scrotal swelling with hydrocoele, although, a variety of other genital manifestations can also be seen. This study was undertaken to establish the clinicopathological spectrum of chronic filarial epididymo-orchitis (FEO) in a tertiary care institution in India. Methods: Cross-sectional observational study spanning a retrospective period of 17 years from 2000-2017. Results: Nineteen cases of chronic FEO were diagnosed, comprising 1.8% of all testicular and paratesticular biopsies (n=1055). Median age was 40 years. All patients presented with scrotal swelling. Examination revealed hydrocoele (12/19), lymph scrotum (5/19), epididymal nodules (4/19) or scrotal elephantiasis mimicking testicular tumour (3/19). Gross examination of orchidectomy specimens revealed cystic hydrocoele sacs with markedly thickened tunica, while four cases showed extensive parenchymal necrosis. Histopathology revealed adult filarial worms either within the epididymal/paratesticular tissues (9/19) or in the tunica vaginalis (7/19). Two cases, in addition, showed microfilarial larvae within the tissues. Six cases showed characteristic Meyers-Kouvenaar bodies surrounding adult worms. Conclusion: This single institution study from India identifies chronic FEO as a rare but important cause of scrotal swelling. Since chronic FEO may be clinically mistaken for testicular tumour, awareness of the clinicopathological spectrum is essential. Biopsies with intense infiltrate of eosinophils and lymphangiectasia need high index of suspicion for filariasis and warrant careful search for adult filarial worm as well as microfilaria in tissue sections.